Action dynamics reveal two types of cognitive flexibility in a homonym relatedness judgment task - Dshemuchadse, Maja; Grage, Tobias; Scherbaum, Stefan (Frontiers in Psychology, 2015)
Cognitive flexibility is a central component of executive functions that allow us to behave meaningful in an ever changing environment. Here, we support a distinction between two different types of cognitive flexibility, shifting flexibility and spreading flexibility, based on independent underlying mechanisms commonly subsumed under the ability to shift cognitive sets. We use a homonym relatedness judgement task and combine it with mouse tracking to show that these two types of cognitive flexibility follow independent temporal patterns in their influence on participants’ mouse movements during relatedness judgments. Our results are in concordance with the predictions of a neural field based framework that assumes the independence of the two types of flexibility. We propose that future studies about cognitive flexibility in the area of executive functions should take independent types into account, especially when studying moderators of cognitive flexibility.